Segregation and Homeownership in the Early Twentieth Century - Logan, Trevon D.; Parman, John M. (American Economic Review, 2017)
We use new county-level segregation estimates for the period of 1880 to 1940 to document a general rise in residential segregation in both urban and rural counties occurring alongside rising homeownership rates. However, we find a negative correlation between segregation and homeownership across space for both black and white households. Following Fetter (2013), we show that living in a more segregated county substantially reduced the impact of GI Bill benefits on white homeownership rates, suggesting that segregated locations potentially hindered both white and black homeownership.